Post-Crash Economics Plurality and Heterodox Ideas in Teaching and Research (Springer International Publishing, 2018)
This book demonstrates the continuing relevance of economics for understanding the world, through a restatement of the importance of plurality and heterodox ideas for teaching and research. The Great Financial Crash of 2007-8 gave rise to a widespread critique of economics for its inability to explain the most significant economic event since the 1930s. The current straightjacket of neo-classical undergraduate economic teaching and research hinders students' understanding of the world they live in. The chapters in this book provide examples to demonstrate the importance of pluralistic and heterodox ideas from across the breadth of economics. The authors' plurality of approach is indicative of the fact that economics is a much broader discipline than the dominant neo-classical orthodoxy would suggest. This volume provides undergraduate students with a range of alternative ideas and university lecturers with examples whereby the curricula have been broadened to include pluralist and heterodox ideas. The quest for a rethinking of the university Economics curriculum has produced a lively and dynamic literature. This book goes further than others by exploring how heterodox approaches would enrich the syllabus not only in micro and macro economics but also in business, development and financial economics. It also considers approaches for engaging students with the Economics discipline. This book is essential for scholars and instructors who advocate a new curriculum if Economics is to be relevant for the real world. ___Alberto Paloni, University of Glasgow.